2018
DOI: 10.1590/0001-3765201820170313
|View full text |Cite
|
Sign up to set email alerts
|

Growth of tree species and sugarcane production in agroforestry systems

Abstract: The appropriate choice of tree species and planting arrangement for use in agroforestry systems is very important in order to maximize productivity and sustainability. The aim of this study was to evaluate the growth of five tree species and its effect on sugarcane yields in different planting arrays in agroforestry systems. The study was conducted from 2007 to 2011 in the city of Frederico Westphalen, RS, Brazil. The five studied tree species were: guapuruvu (Schizolobium parahybae), bracatinga (Mimosa scabre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Conversely, solar radiation was the variable with the lowest participation in the models, indicating a secondary effect of this variable on the productivity of sugarcane in Rio Grande do Sul. CARON et al (2018) evaluated the productivity of sugarcane in agroforestry systems and reported productivity above 60 tons of stalks per hectare, which is compatible with the average for southern Brazil (CONAB, 2018) when cultivated under a reduction of 20% in the incidence of solar radiation. Therefore, these results corroborated those observed in this study, which showed that solar radiation was not the main determinant of sugarcane productivity.…”
Section: Resultsmentioning
confidence: 68%
“…Conversely, solar radiation was the variable with the lowest participation in the models, indicating a secondary effect of this variable on the productivity of sugarcane in Rio Grande do Sul. CARON et al (2018) evaluated the productivity of sugarcane in agroforestry systems and reported productivity above 60 tons of stalks per hectare, which is compatible with the average for southern Brazil (CONAB, 2018) when cultivated under a reduction of 20% in the incidence of solar radiation. Therefore, these results corroborated those observed in this study, which showed that solar radiation was not the main determinant of sugarcane productivity.…”
Section: Resultsmentioning
confidence: 68%
“…Agroforestry systems are those where an agricultural crop coexists with another forest crop, in arrangements optimized for the land use, nutrients and especially sunlight. In Brazil, studies of agroforestry arrangements with sugarcane were carried out, as in the works of Schwerz [34] , Schwerz et al [35] , Schwerz et al [21] , Caron et al [36] , Elli et al [37] and Pinto et al [38] .…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the planting arrangements of each AS and the plasticity of the characteristics of the maize plants are determined by the variety of environmental conditions that prevail in the AS [ 22 ]. For example, Caron et al [ 41 ] found that the high growth rate of Eucalyptus reduced the stem weight of S . officinarum by 50%, attributing this discrepancy to interspecific competition, particularly due to the interception of solar radiation by the crop.…”
Section: Discussionmentioning
confidence: 99%